How Greens turn gray: Green Party politics and the depoliticization of energy and climate change - Marquardt, Jens (Frontiers in Political Science, 2024)
Decarbonization efforts and sustainability transformations represent highly contested socio-political projects. Yet, they often encounter various forms of depoliticization. This article illuminates how a grand socio-ecological challenge like the energy transition gets depoliticized by an unusual suspect, namely the Green Party. I trace how Germany’s Green Party has depoliticized the energy transition over time, emphasizing a shift from radical societal change to ecological modernization. The changing stance of the German Greens on the country’s energy transition reflects more profound changes of a future society the party collectively envisions. These changes result from a struggle between moderates advocating incremental political reforms and radicals aiming for more fundamental societal change. By merging sustainability transition research with science and technology studies, this article makes a two-fold contribution: First, it proposes a conceptual framework to investigate social and political futures envisioned through energy and climate politics. Second, the article empirically demonstrates the long process of depoliticization for an unusual but critical case. Green Party programs, party conventions, and additional documents published between 1980 and 2021 allow us to discuss how the Green Party has embraced a technocentric vision of the energy transition, thereby suppressing earlier notions of broader societal change, such as anti-capitalism and energy democracy. This article spells out implications for the wider field of energy and climate politics and concludes with suggestions for future research.